Educating General Practitioners about Medication-overuse Headache: Importance and Call to Action - Sofyan, Henry Riyanto; Madjid, Irma Savitri; Faiq, Ahmad Rafi; Indrapriambada, Ery Riady; Humaira, Sarah; Aninditha, Tiara (Acta Neurologica Indonesia, 2025)
Medication overuse headache (MOH) is a secondary headache that frequently accompanied chronic primary headaches which poses a great burden in an individual and systemic level. Globally, it is recognized as one of the relevant headaches for primary care. However, in Indonesia, it has not been included in the standard competence for doctors, and therefore has been underrecognized by general practitioners who encountered headache patients in primary care. In this policy brief, we mapped the problems regarding MOH and proposed several action plans, including educating GPs, as the recommendations.